Peran Lisosom dalam Autophagy sebagai Mekanisme Seluler dalam Bertahan dari Stres Nutrisi - Nurdin, Rizky Aprilliani; Masdar, Rinaldi; Adnan (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2025)
Lysosomes function to degrade and recycle cellular components using enzymes that operate in an acidic environment. This organelle helps break down proteins and damaged organelles, supporting cellular renewal through autophagy. Autophagy is a cellular stress response, particularly during nutrient or growth factor deprivation, where intracellular components are recycled to supply energy and raw materials. The regulation of autophagy is controlled by mTOR and AMPK, which respond to the cell’s nutritional status. Previous studies have shown that autophagy is essential for cellular homeostasis and is linked to various diseases, including neurodegenerative disorders, cancer, and aging. In animal models, autophagy gene deficiencies can result in poor metabolism and early death. Research has also demonstrated how autophagy aids in clearing damaged mitochondria, paving the way for potential treatments for degenerative diseases. This study uses meta-analysis of various research findings to synthesize insights on lysosomes and autophagy under nutritional stress. Data were collected from relevant studies and analyzed statistically to assess the consistency of findings and the factors influencing autophagy. The meta-analysis aims to reinforce the connection between nutrient stress and autophagy and to evaluate the therapeutic potential of autophagy modulation. Results indicate that increased autophagy during nutrient stress can protect cells but may also contribute to disease pathology if not properly regulated. Therefore, further research into autophagy mechanisms and their therapeutic potential is necessary.